Miniaturized Needle Array‐Mediated Drug Delivery Accelerates Wound Healing. Issue 8 (15th February 2021) - Samandari, Mohamadmahdi; Aghabaglou, Fariba; Nuutila, Kristo; Derakhshandeh, Hossein; Zhang, Yuteng; Endo, Yori; Harris, Seth; Barnum, Lindsay; Kreikemeier‐Bower, Craig; Arab‐Tehrany, Elmira; Peppas, Nicholas A.; Sinha, Indranil; et al.
Abstract: A major impediment preventing normal wound healing is insufficient vascularization, which causes hypoxia, poor metabolic support, and dysregulated physiological responses to injury. To combat this, the delivery of angiogenic factors, such as vascular endothelial growth factor (VEGF), has been shown to provide modest improvement in wound healing. Here, the importance of specialty delivery systems is explored in controlling wound bed drug distribution and consequently improving healing rate and quality. Two intradermal drug delivery systems, miniaturized needle arrays (MNAs) and liquid jet injectors (LJIs), are evaluated to compare effective VEGF delivery into the wound bed. The administered drug's penetration depth and distribution in tissue are significantly different between the two technologies. These systems' capability for efficient drug delivery is first confirmed in vitro and then assessed in vivo. While topical administration of VEGF shows limited effectiveness, intradermal delivery of VEGF in a diabetic murine model accelerates wound healing. To evaluate the translational feasibility of the strategy, the benefits of VEGF delivery using MNAs are assessed in a porcine model. The results demonstrate enhanced angiogenesis, reduced wound contraction, and increased regeneration. These findings show the importance of both therapeutics and delivery strategy in wound healing. Abstract : The effect of vascular endothelial growth factor (VEGF) delivered intradermally using liquid jet injectors and miniaturized needle arrays on wound healing is investigated in mouse and pig models. Miniaturized needle arrays facilitate proper drug distribution within the tissue and improve the rate and quality of wound healing.